The Influence of the MIKiR Learning Model on the Ability to Write Drama Scripts for Class VIII Students of AL-Hikmah Medan Middle School for the 2022/2023 Academic Year - Damayanti, Indah; Izar, Sri Listiana (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2023)
The purpose of this study was to determine the ability to write drama scripts before and after using the scientific approach in class VIII students of SMP AL- Hikmah Medan in the 2022/2023 Learning Year. This research is experimental research where the object studied is the VIII grade students of SMP AL-Hikmah Medan for the 2022/2023 Learning Year. The results showed that before using the MIKiR learning model, the average pre-test score of class VIII-5 was 51.22 or in the poor category, and the standard deviation was 8.82. Based on the research results after using the MIKiR learning model in class VIII-5, the average score was 80.11 or in the good category, and the standard deviation was 13.59. In the pre-test learning there was 1 student who met the Minimum Completeness Criteria (KKM) or who reached a score of 75, while 34 students did not meet the KKM. In the post-test learning there were 28 students who met the KKM while 7 other students did not pass the KKM. Based on the calculation of the hypothesis test, the tcount is 96.3 and if you look at the ttable value at a significant level of 0.05 and df = N -1, 35-1 = 34, the ttable is 1.69. By comparing thitung with ttabel using the criteria thitung > ttabel (96.3> 1.69), then Ha is accepted. In other words, there is an effect of the MIKiR learning model on the learning outcomes of the ability to write drama scripts of class VIII students of SMP AL- Hikmah Medan in the 2022/2023 learning year.